2016
DOI: 10.4314/ahs.v16i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Cell phone–based health education messaging improves health literacy

Abstract: Background: The ubiquity of cell phones, which allow for short message service (SMS), provides new and innovative opportunities for disease prevention and health education. Objective: To explore the use of cell phone-based health education SMS to improve the health literacy of community residents in China. Methods: A multi-stage random sampling method was used to select representative study communities and participants ≥ 18 years old. Intervention participants were sent health education SMSs once a week for 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…Of the 22 included studies, the earliest study was from 2014 [30], the latest from 2020 [35][36][37] with the majority (fourteen) being published since 2018 [32-37, 44, 45, 47-52]. Eighteen studies were randomised and included 1 cross over design [50], 5 cluster randomised [39,41,44,47,51] and 12 individually randomised trials [30-32, 34, 36-38, 40, 43, 45, 49, 52]. The remaining four were quasi-experimental pre-post controlled trials [33,35,42,48].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 22 included studies, the earliest study was from 2014 [30], the latest from 2020 [35][36][37] with the majority (fourteen) being published since 2018 [32-37, 44, 45, 47-52]. Eighteen studies were randomised and included 1 cross over design [50], 5 cluster randomised [39,41,44,47,51] and 12 individually randomised trials [30-32, 34, 36-38, 40, 43, 45, 49, 52]. The remaining four were quasi-experimental pre-post controlled trials [33,35,42,48].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The remaining four were quasi-experimental pre-post controlled trials [33,35,42,48]. Studies took place in nine countries -USA [30,31,37,39,40,42,43,45], Australia [35,51,52], Iran [32,34,47], China [41,44], Japan [36,49], Taiwan [48], Niger [38], Germany [50] and Demark [33].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized trials indicated mobile phone reminder improves appointment compliance [20,23,24], adherence to ART and Tb medications [25,26]. In addition, it facilitates provision of health education, counseling [27,28] and behavioral change interventions [17,29].…”
Section: Introductionmentioning
confidence: 99%
“…a focus on HIV and sexual health). It is possible that response may increase with greater interaction, on-demand information and variation in delivery, through algorithmic approaches to text message replies, custom SMS gateways or peer led two-way SMS services although these approaches would occur an increased manpower and/or software development cost, contrary to the low cost appeal of SMS interventions [23,86].…”
Section: Discussionmentioning
confidence: 99%